2008
DOI: 10.2478/v10007-008-0026-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ampicillin and chloroquine on humoral immune response elicited by bovine albumin encapsulated in liposomes

Abstract: Several studies have been conducted to establish the phenomenon of vaccine-drug interaction against various categories of chemotherapeutic agents, such as fluoroquinolones and chloramphenicol (1). They can either increase or decrease the phagocytic function or modulate the immune response triggered by an antigen (2). Investigations have revealed that chloroquine prophylaxis for malaria is associated with an impaired antibody response to rabies vaccine administered intradermally (3). It was proposed that chloro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…It was observed that 99% of peptides in their free form were released within 6 h, while peptides from niosomes showed the burst release to the extent of 41% during the first hour of dialysis under simulated GI conditions (pH of 1.2) because of the fast diffusion of peptide molecules located on the surface, followed by controlled release under simulated intestinal conditions (pH 7.4). This kind of protein release profile has also been observed for BSA-loaded niosomal vesicles. , The initial burst release was presumably due to the presence of peptides in the free form in the niosomes, while the sustained release to the extent of 85.54% by 24 h was probably due to their encapsulation into niosomal bilayers. Raslan showed that the profile of ketoprofen release from niosomes occurred in two distinct phases; an initial phase in which rapid drug leakage was observed in the first 6 h to the extent of 50–60%, followed by slow release of only 20% in the next 6 h. Moreover, proteins such as insulin encapsulated in niosomal vesicles showed a similar sustained release .…”
Section: Results and Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…It was observed that 99% of peptides in their free form were released within 6 h, while peptides from niosomes showed the burst release to the extent of 41% during the first hour of dialysis under simulated GI conditions (pH of 1.2) because of the fast diffusion of peptide molecules located on the surface, followed by controlled release under simulated intestinal conditions (pH 7.4). This kind of protein release profile has also been observed for BSA-loaded niosomal vesicles. , The initial burst release was presumably due to the presence of peptides in the free form in the niosomes, while the sustained release to the extent of 85.54% by 24 h was probably due to their encapsulation into niosomal bilayers. Raslan showed that the profile of ketoprofen release from niosomes occurred in two distinct phases; an initial phase in which rapid drug leakage was observed in the first 6 h to the extent of 50–60%, followed by slow release of only 20% in the next 6 h. Moreover, proteins such as insulin encapsulated in niosomal vesicles showed a similar sustained release .…”
Section: Results and Discussionsupporting
confidence: 63%
“…This kind of protein release profile has also been observed for BSA-loaded niosomal vesicles. 28,51 The initial burst release was presumably due to the presence of peptides in the free form in the niosomes, while the sustained release to the extent of 85.54% by 24 h was probably due to their encapsulation into niosomal bilayers. Raslan 52 showed that the profile of ketoprofen release from niosomes occurred in two distinct phases; an initial phase in which rapid drug leakage was observed in the first 6 h to the extent of 50−60%, followed by slow release of only 20% in the next 6 h. Moreover, proteins such as insulin encapsulated in niosomal vesicles showed a similar sustained release.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…1) (31). Briefly, set amounts of Span 60 (Table I) with different percentages of CH (0%, 20%, 40%, 60%, and 80%) (Table II) were dissolved in 5 ml of diethyl ether.…”
Section: Preparation Of Bsa-loaded Niosomesmentioning
confidence: 99%
“…Few experimental studies have been published on immune disturbance of chloramphenicol, and these studies did not follow the systematic immunotoxicity protocols as is currently customary for immunotoxicity risk assessment, including quantitative aspects (WHO, 2012). Madan et al (2007) studied antibody production in male albino rats (8-12 weeks of age) after s.c. bovine serum albumin (BSA) immunisation, following treatment with ciprofloxacin (i.m. administration of 0.33 mg/kg b.w.…”
Section: Immunotoxicity Based On Immune Function Testsmentioning
confidence: 99%